A Critical Perspective on the Regulation Regarding the Benefit of the Same Rights as Turkish Citizens by Blue Card Holders - Necla Öztürk (Public and Private International Law Bulletin)
The Turkish legislature needs to enact a regulation that would allow Turkish nationals living in countries with significant populations of Turkish citizens, such as Germany, Belgium, and Austria, to continue to be treated like Turkish citizens, although with some exceptions for those who renounced their citizenship when obtaining their permission to leave Turkey. To address this, a regulation was placed into effect for the first time in 1995 and amended in t 2004, 2009, and 2012 in response to changes in factual circumstances related to the regulation. With the promulgation of these regulations, a special foreigner status group, termed blue cardholders, was created and purportedly defined the rights of the blue cardholders. However, in practice, the problems remain to be resolved. The main reason for these problems is the difference in the interpretation of the broad but ambiguous statement “they enjoy the same rights that are given to Turkish citizens” in the positive regulation. The best way to solve the problems created by this situation is to revise this provision to regulate the status and rights of blue cardholders with specificity.